2019
DOI: 10.1002/ejoc.201900719
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Michael Addition of Aldehydes to β‐Nitrostyrenes Catalyzed by (S)‐N‐(D‐Prolyl)‐1‐triflicamido‐3‐phenylpropan‐2‐amine

Abstract: A new organocatalyst for the asymmetric Michael addition reaction of aldehydes with β‐nitrostyrenes is developed by coupling D‐proline with (S)‐1‐triflicamido‐3‐phenylpropan‐2‐amine, which in turn is prepared from L‐phenylalaninol. The Michael addition products were obtained in very high yields (up to 93 %) and with excellent enantioselectivity (up to 97 % ee) and high diastereoselectivity (up to >99:1 dr). The catalyst is effective for reactions between α‐branched aldehydes and β‐nitrostyrenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…Amol B. Gorde and Ramesh Ramapanicker [38] developed an organocatalyst ( s )‐N‐( d ‐prolyl)‐1‐triflicamido‐3‐phenylpropan‐2‐amine VII for stereoselective Michael addition of aldehydes 6 to 19 in presence of toluene in 2019. In excellent yields (up to 93 %), Michael addition adducts 20 were afforded with high diastereo‐ (up to >99 : 1 dr) and enantio‐ selectivities (up to 97 %) [Scheme 8].…”
Section: Organocatalytic Enantioselective Michael Addition Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amol B. Gorde and Ramesh Ramapanicker [38] developed an organocatalyst ( s )‐N‐( d ‐prolyl)‐1‐triflicamido‐3‐phenylpropan‐2‐amine VII for stereoselective Michael addition of aldehydes 6 to 19 in presence of toluene in 2019. In excellent yields (up to 93 %), Michael addition adducts 20 were afforded with high diastereo‐ (up to >99 : 1 dr) and enantio‐ selectivities (up to 97 %) [Scheme 8].…”
Section: Organocatalytic Enantioselective Michael Addition Reactionsmentioning
confidence: 99%
“… ( s )‐N‐( d ‐prolyl)‐1‐triflicamido‐3‐phenylpropan‐2‐amine catalyzed Michael addition reactions of aldehydes to β ‐nitrostyrenes [38] …”
Section: Organocatalytic Enantioselective Michael Addition Reactionsmentioning
confidence: 99%
“…[ 6 ] However, sterically hindered carbonyl compounds, such as α‐branched aldehydes, ketones, and their α,β‐unsaturated counterparts, are usually less reactive or even inert to secondary amines, probably because the bulky substituents impede the formation of iminium ion/enamine intermediates (Scheme 2, right). [ 7 ] In 2005, Ishihara disclosed that primary amines prepared from dipeptides could effectively activate α‐substituted acroleins by forming the corresponding iminium ions for subsequent normal electron demanding Diels–Alder (NEDDA) reaction with electron‐rich dienes. [8] Later, the mechanism study demonstrated that compared with secondary amines, primary amines are more easy to condense with hindered aldehydes and ketones, due to their structural and conformational flexibility (Scheme 2, Left).…”
Section: Development and Application Of Cinchona Alkaloid‐ Based Primary Amine Catalystsmentioning
confidence: 99%
“…Ramapanicker et al ., [43] developed a series of proline‐prolinol catalysts derived from dipeptide catalysts (for instance, 53 a in Figure 9) for conjugate addition reactions based on two aspects. A proline‐based framework along with NHTf group as hydrogen bond donors instead of carboxylic acid or phosphonic acid.…”
Section: Proline‐dipeptide Derived Catalystsmentioning
confidence: 99%